Randomised comparative study on the efficacy of 3% versus 30% NaCl solution in the treatment of umbilical granuloma - Janyoungsak P. (2023)
Aim: This study aimed to compare the efficacy of 3% versus 30% NaCl solution in treating umbilical granuloma (UG) and to evaluate parental satisfaction. Methods: A randomised, double-blinded, comparative study in neonates with UG was conducted. Stratified, block-of-four randomisation was used to allocate neonates into two groups, treated with 3% or 30% pharmaceutical-grade NaCl solution, three times daily. The time to resolution was determined by daily photographs of UG and weekly hospital visits. If there was no response after 2 weeks, silver nitrate was used. Parental satisfaction was measured on a rating scale of 1–5. Results: One hundred neonates were enrolled, 48 in the 3% NaCl group and 52 in the 30% NaCl group. Baseline demographic data were not different between the groups. There was no significant difference in the resolution rate (93.8% vs 98.1%) or the median (interquartile range) time to resolution (7 (5–13) vs 7 (4–11) days) between the 3% and 30% NaCl groups, respectively. No skin burn or cellulitis was detected. About 95% of parents scored >4 for satisfaction. Conclusions: Hypertonic NaCl solution is highly effective in treating UG without side effects. Hypertonic NaCl solution should be considered as an alternative treatment for UG.